Epidemiology, Risk Factors, and Predictors of Disability in a Cohort of Jordanian Patients with the First Ischemic Stroke - Majdi Al Qawasmeh; Belal Aldabbour; Aiman Momani; Deema Obiedat; Kefah Alhayek; Raid Kofahi; Ahmed Yassin; Khalid El-Salem (Stroke Research and Treatment)
Objective. To identify the risk factors, etiologies, length of stay, severity, and predictors of disability among patients with the first ischemic stroke in Jordan. Methods. A retrospective cohort study of 142 patients who were admitted to the Neurology Department at King Abdullah University Hospital between July/2017 and March/2018 with a first ischemic stroke. Etiology was classified according to the TOAST criteria. Severity was represented by NIHSS score, disability by mRS score, and prolonged length of stay as hospitalizations more than 75th percentile of the cohort’s median length of stay. Analysis of the sample demographics and descriptive statistics were done, including frequencies of prevalence of independent variables (risk factors) and frequencies of stroke and etiology work-up. Chi-square and univariate analysis of variance “ANOVA” were used to investigate the relationship between risk factors and type of stroke. Finally, logistic regression analysis was used to measure the contribution of each of the independent variables. IRB approval was obtained as necessary. Results. The mean age for the cohort was 66.5 years. The most common risk factors were hypertension (78.8%), diabetes mellitus (60.5%), and ischemic heart disease (29.4%). The most common stroke etiology was small-vessel occlusion (54.2%). Median length of stay was 4 days. Prolonged length of stay was observed in 23.23% of patients, which was associated with several factors, the most common of which were persistent dysphagia (57.5%), nosocomial infection (39.3%), and combined dysphagia and nosocomial infection (21.2%). The mean admission NIHSS score was 7.94, and on discharge was 5.76. In-hospital mortality was 2.81%, while 50% of patients had a favorable outcome on discharge (mRS score between 0-2). The mean discharge mRS score for the cohort was 2.47 (SD±1.79). Large artery atherosclerosis was associated with the highest residual disability with a mean score of 3.67 (SD±1.88), while the stroke of undetermined etiology was associated with the lowest residual disability with a mean score of 1.60 (SD±1.78). Significant predictors of mRS score were smoking (t 3.24, P<0.001), age (t 1.98, P<0.049), and NIHSS score (t 9.979, P 0.000). Conclusion. Ischemic strokes have different etiologies that are associated with different levels of impact on the patient’s clinical status and prognosis. Large artery atherosclerosis was associated with the highest residual disability. Regarding predictors of prognosis, current smoking status, age above 50, gender, and NIHSS on admission appear to be the strongest predictors of prognosis. Finally, higher NIHSS score on admission resulted in a longer hospital stay.